Processing pro-drop features in heritage Turkish - Uygun, Serkan (Frontiers in Psychology, 2022)
Previous studies have reported that null subject is not completely lost in heritage speakers, but there is an increase in the production and acceptance of overt subjects. Turkish is a pro-drop language and as a typical feature of pro-drop languages, it requires obligatory verb agreement marking for sentences with null subjects. However, Turkish subject-verb agreement marking is an example of optional agreement in which the 3rd person plural subject has optionality and can be used with singular verb forms under certain conditions. The current study investigates the reading times (RTs) of plural-marked and unmarked verbs in sentences with overt and null subjects during real time sentence processing in comparison to non-heritage speakers of Turkish via a self-paced reading experiment. Significant differences were observed between the heritage and non-heritage speakers of Turkish indicating both quantitative and qualitative real-time processing differences between the two groups. These differences suggest that Turkish heritage speakers need more time to integrate the information in real time processing.